Ankle joint dislocation treating dislocated trimalleolar fractures accompanied with the complex posterior malleolus fracture without separation of the tibiofibular syndesmosis - Xing, Wenzhao (Medicine (Baltimore), 2018)
To explore the therapy of ankle joint dislocation treating dislocated trimalleolar fractures accompanied with the complex posterior malleolus fracture without separation of the tibiofibular syndesmosis and improve surgical results. Patients who had dislocated trimalleolar fractures accompanied with the complex posterior malleolus fracture without separation of the tibiofibular syndesmosis were retrospectively analyzed and 30 patients were enrolled the study. They were all treated by ankle joint dislocation and the surgical results were evaluated by the Baird–Jackson ankle scoring system. Longitudinal curved incision in medial malleolus was made in ankle joint dislocation and subluxation was automatically formed by appropriate traction of ankle joint. The talus and the distal end of internal and external malleolus were pushed the outside to form the lateral dislocation of the ankle joint. After fully revealed the posterior malleolus and distal articular surface of the tibia, the anatomical reduction of comminuted bones with joint cartilage and posterior malleolus was achieved by fixed with absorbable screw or Kirschner wire. Internal and external malleolus fracture was fixed by the conventional approach. The average follow-up period was 13 months. According to the Baird–Jackson ankle scoring system, the excellent and good result was 28 cases, fair was 2 cases which the excellent and good rate was 93.3% without talar necrosis in any cases. Ankle joint dislocation can achieve the satisfactory results in treating dislocated trimalleolar fractures accompanied with the complex posterior malleolus fracture without separation of the tibiofibular syndesmosis. Ankle joint dislocation can make joint cartilage restore accurately with excellent results.